“From Gamers into Environmental Citizens”: A Systematic Literature Review of Empirical Research on Behavior Change Games for Environmental Citizenship - Georgiou, Yiannis; Hadjichambis, Andreas Ch.; Paraskeva-Hadjichambi, Demetra; Adamou, Anastasia (My University, 2023)
As the global environmental crisis intensifies, there has been a significant interest in behavior change games (BCGs), as a viable venue to empower players’ pro-environmentalism. This pro-environmental empowerment is well-aligned with the notion of environmental citizenship (EC), which aims at transforming citizens into “environmental agents of change”, seeking to achieve more sustainable lifestyles. Despite these arguments, studies in this area are thinly spread and fragmented across various research domains. This article is grounded on a systematic review of empirical articles on BCGs for EC covering a time span of fifteen years and published in peer-reviewed journals and conference proceedings, in order to provide an understanding of the scope of empirical research in the field. In total, 44 articles were reviewed to shed light on their methodological underpinnings, the gaming elements and the persuasive strategies of the deployed BCGs, the EC actions facilitated by the BCGs, and the impact of BCGs on players’ EC competences. Our findings indicate that while BCGs seem to promote pro-environmental knowledge and attitudes, such an assertion is not fully warranted for pro-environmental behaviors. We reflect on our findings and provide future research directions to push forward the field of BCGs for EC.
Keywords: behavior change; environmental citizenship; pro-environmentalism; serious games; systematic review